Up-regulation of NMRK2 mediated by TFE3 fusions is the key for energy metabolism adaption of Xp11.2 translocation renal cell carcinoma. (10th July 2022) - Chen, Yi; Yang, Lei; Lu, Yanwen; Liu, Ning; Ma, Wenliang; Fan, Hanqi; Hu, Qingquan; Han, Xiaodong; Gan, Weidong; Li, Dongmei
Abstract: Due to the inadequate awareness of Xp11.2 translocation renal cell carcinoma (Xp11.2 tRCC), its metabolic features have not been described. Here, by using nontargeted LC–MS-based metabolomics, we found that the chimeric TFE3 protein, the major oncogenic driver in Xp11.2 tRCC, regulated the metabolic pathways in Xp11.2 tRCC, including glycerophospholipid metabolism, purine metabolism, amino acid metabolism, fatty acid metabolism and energy metabolism. Combined with our present metabolomic data and previous studies, it was found that Xp11.2 tRCC preferred mitochondrial respiration, which was obviously different from renal clear cell carcinoma (ccRCC). Furthermore, by using bioinformatics and data mining, NMRK2, an important target for energy metabolism adaptation of Xp11.2 tRCC, was identified. Additionally, we confirmed that chimeric TFE3 could transcriptionally activate the expression of NMRK2, but the NONO-TFE3 fusion, which lacks the activation domain encoded by exons 4–5 of the TFE3 gene, functioned as a transcription factor by recruiting TFEB. When NMRK2 was knocked down, the mitochondrial respiration of Xp11.2 tRCC, rather than glycolysis, was significantly weakened. Therefore, the present study revealed the mechanism of the energy metabolism adaptation by which the TFE3 fusion promotes mitochondrial respiration by upregulating NMRK2 in Xp11.2 tRCC. Highlights: Xp11.2 tRCC showed a preference for mitochondrial respiration regulated by chimeric TFE3 protein. NMRK2 was the specific target gene of chimeric TFE3 protein, and might serve as a novel target for therapy. NMRK2 play central role in promote the progression of oxidative phosphorylation in Xp11.2 tRCC. NONO-TFE3 fusion transcriptionally activated NMRK2 by recruiting TFEB.